Kemampuan Berbahasa Pada Anak Penderita Tunagrahita Berat Studi Kasus: Nurhuda Surya Finingsih di SLB Negeri 1 Padang - Anita Angraini Lubis; Erna Ikawati (Jurnal Kajian Gender dan Anak, 2020)
The purpose of this study was to describe the language skills that can be produced by a child with severe intellectual disability at SLB N 1 Padang . The method and technique used in this study were the referral method for the data collection stage with tapping techniques as basic techniques and advanced techniques of proficient involvement (SLC), proficient non-active listening (SBLC), notes, and records. Articulatory equivalent method for data analysis stage, and formal and informal presentation methods for the presentation phase of data analysis results. This study found that children's productive abilities are still very minimal and require rigorous training and long time so that they can make a change in language for children. Teachers and parents should also continue to train children with discipline. The ability to write to a new child at the stage of connecting the dots forms a phoneme. Cici hasn't been able to make one fonem well without being helped by dots. Cici hasn't been able to read, count, and doesn't like drawing. Then, there may be a nerve problem in the child's brain that causes his hands and fingers to always vibrate. His emotional state at any time can peak and uncontrollable.